Evaluation of preoperative high magnetic field motor functional MRI (3 Tesla) in glioma patients by navigated electrocortical stimulation and postoperative outcome. Issue 8 (15th July 2005) - Roessler, K; Donat, M; Lanzenberger, R; Novak, K; Geissler, A; Gartus, A; Tahamtan, A R; Milakara, D; Czech, T; Barth, M; Knosp, E; Beisteiner, R
Abstract : Objectives: The validity of 3 Tesla motor functional magnetic resonance imaging (fMRI) in patients with gliomas involving the primary motor cortex was investigated by intraoperative navigated motor cortex stimulation (MCS). Methods: Twenty two patients (10 males, 12 females, mean age 39 years, range 10–65 years) underwent preoperative fMRI studies, performing motor tasks including hand, foot, and mouth movements. A recently developed high field clinical fMRI technique was used to generate pre-surgical maps of functional high risk areas defining a motor focus. Motor foci were tested for validity by intraoperative motor cortex stimulation (MCS) employing image fusion and neuronavigation. Clinical outcome was assessed using the Modified Rankin Scale. Results: FMRI motor foci were successfully detected in all patients preoperatively. In 17 of 22 patients (77.3%), a successful stimulation of the primary motor cortex was possible. All 17 correlated patients showed 100% agreement on MCS and fMRI motor focus within 10 mm. Technical problems during stimulation occurred in three patients (13.6%), no motor response was elicited in two (9.1%), and MCS induced seizures occurred in three (13.6%). Combined fMRI and MCS mapping results allowed large resections in 20 patients (91%) (gross total in nine (41%), subtotal in 11 (50%)) and biopsy in two patients (9%). Pathology revealed seven low grade and 15 high grade gliomas. Mild to moderate transient neurological deterioration occurred in six patients, and a severe hemiparesis in one. All patients recovered within 3 months (31.8% transient, 0% permanent morbidity). Conclusions: The validation of clinically optimised high magnetic field motor fMRI confirms high reliability as a preoperative and intraoperative adjunct in glioma patients selected for surgery within or adjacent to the motor cortex.